Acute and chronic rhinosinusitis – treatment - Kukwa, Wojciech; Jeżewska, Elżbieta; Ścińska, Anna; Kukwa, Andrzej; Żulewska, Nina (Przewodnik Lekarza/Guide for GPs, 2006)
Authors present latest opinions about the pathogenesis of rhinosinusitis, the symptomatolgy, diagnostic tools and therapeutic methods. Both the acute and chronic rhinusinusitis are discussed.